Integrating Local Wisdom in Science: Development and Validation of Ethnoscience Teaching Modules for Improving Science Literacy of Junior High School Students - Sutanto, Taufiq; Akhsan, Hamdi; Kistiono, Kistiono (Integrated Science Education Journal, 2026)
Purpose of the study: The low level of science literacy among Indonesian students requires innovative and contextual learning approaches. This study aims to develop and test the validity of an Ethnoscience-Based Teaching Module on the subject of Vibrations and Waves. The uniqueness of the module lies in its deep integration of the local wisdom of East OKU Regency as a learning context to bridge abstract scientific concepts with the cultural reality of students. Methodology: This study used the Research and Development (R&D) method with a 4-D model, limited to the Develop stage. Validation was carried out by four experts (material, media, language, and culture) using adapted assessment instruments. Quantitative data were analyzed using Aiken's V coefficient. Main Findings: The developed ethnoscience-based teaching module was declared "Highly Valid" with an average Aiken’s V score of 0.90. All validation aspects scored highly: subject matter (0.90), media design (0.88), language (0.85), and cultural integration (0.95). The module is therefore feasible for further testing. Novelty/Originality of this study: The developed module has met the eligibility criteria in terms of content, design, language, and authentic cultural integration. The implication of this research is the availability of valid and contextual teaching materials, which are ready to be further tested for their effectiveness in learning to improve science literacy while building students' cultural awareness.